How do dinosaurs go to school? - Yolen, Jane.; Teague, Mark (New York : Blue Sky Press, 2007)
Ten dinosaurs show that while they have the potential to create mischief at school, they know how to control themselves.
Booklist.
Publisher's Weekly.
School Library Journal.
2.2
K-3
Keywords: Dinosaurs -- Juvenile fiction; Human behavior -- Juvenile fiction; Schools -- Juvenile fiction; Behavior -- Fiction; Dinosaurs -- Fiction; Schools -- Fiction; Stories in rhyme; Dinosaurs -- Fiction; Human behavior -- Fiction; School stories; Stories in rhyme